Seismic design of steel structures - Gioncu, Victor; Mazzolani, Federico M. (Boca Raton, [Florida] : CRC Press/Taylor & Francis Group, 2014)
'Observation and research into the performance of steel structures during recent large earthquakes, such as those in Mexico City, Loma Prieta, Northridge and Kobe, has produced some very interesting results; not least in emphasising differences in the seismic effects of near-source and far-source earthquakes. Seismic Design of Steel Structures presents a critical review of the huge amount of technical information generated from these observations. The authors consider all types of steel structures, and present a new philosophy for their effective and safe design. In this new design philosophy, the direct checking of structural ductility plays a leading role. Real world applications and are described for different structural types and seismic characteristics, underlining the main features of each. Seismic Design of Steel Structures is a practical reference for all structural engineers involved in seismic design. It will be invaluable to researchers and postgraduate students of seismic structural analysis and design'--
Failure of a myth -- Steel against earthquakes -- Challenges in seismic design -- New generation of steel structures -- Advances in steel beam ductility -- Fire after earthquake.
Includes bibliographical references and index.
Keywords: Building, Iron and steel -- Earthquake effects; Earthquake resistant design; Steel, Structural -- Earthquake effects; Steel, Structural -- Ductility; TECHNOLOGY & ENGINEERING / Construction / General; TECHNOLOGY & ENGINEERING / Engineering (General).; TECHNOLOGY & ENGINEERING / Civil / General